2010
DOI: 10.1159/000313528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation Therapy on Myocardial Cell Integrity and Pump Function: Which Role for Cardiac Biomarkers?

Abstract: Background: Radiation therapy to the mediastinum and breast can be associated with cardiac complications. Cardiac damage may manifest early during radiation therapy or occur late, years after radiation therapy has been finished. Hypothesis: Myocardial damage is associated with the release of both troponin I (TnI) and brain natriuretic peptide (BNP). The current study sought to determine whether radiation treatment to the mediastinum and breast leads to the release of cardiac biomarkers. Methods: The study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Because of the prolonged survival time in cancer patients after thoracic radiotherapy, late-onset cardiac diseases create more problems, which include acute and chronic pericardial disease, cardiomyopathy, valvular dysfunction, conduction abnormalities and coronary artery disease, collectively referred to as radiationinduced heart diseases (RIHD). A recent study (Nellessen et al 2010) found that after radiation therapy of lung cancer and breast cancer, in patients the levels of the cardiac biomarkers troponin I and brain natriuretic peptide increased significantly. This study suggested that serial measurements of cardiac biomarkers might facilitate the management of patients undergoing radiation therapy and might help to define subgroups at high risk of developing heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the prolonged survival time in cancer patients after thoracic radiotherapy, late-onset cardiac diseases create more problems, which include acute and chronic pericardial disease, cardiomyopathy, valvular dysfunction, conduction abnormalities and coronary artery disease, collectively referred to as radiationinduced heart diseases (RIHD). A recent study (Nellessen et al 2010) found that after radiation therapy of lung cancer and breast cancer, in patients the levels of the cardiac biomarkers troponin I and brain natriuretic peptide increased significantly. This study suggested that serial measurements of cardiac biomarkers might facilitate the management of patients undergoing radiation therapy and might help to define subgroups at high risk of developing heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 30 patients receiving thoracic chemoradiation, no significant elevation in creatine kinase-myocardial band (CK-MB), troponin, or NT-pro BNP was detected with radiation therapy [74]. In one study both troponin and BNP increased significantly during the study; however, the absolute and mean values remained on a relatively low level (mean preradiation and postradiation troponin I: 0.007 ± 0.008, 0.014 ± 0.01 ng/mL; mean preradiation and post radiation BNP: 123 ± 147, 159 ± 184 pg/mL) [75]. Hence based on current knowledge, cardiac biomarkers are not recommended for evaluation of radiation-induced cardiotoxicity but remain a useful research tool.…”
Section: Role Of Biomarkers In Patients Undergoing Radiation Therapymentioning
confidence: 99%
“…Thus, the importance of this study is profound, considering few studies have focused on the mechanism by which thoracic radiation alters cardiac blood biomarker levels. [17][18][19][20] Collectively, these results suggest that RT-induced left ventricular dysfunction and myocardial injury can be evaluated by measuring both TnI and BNP levels as well as SRI before and after RT. Furthermore, measurements of both biomarkers and SRI can be utilized to monitor cardiotoxicity and early signs of cardiovascular dysfunction.…”
Section: Introductionmentioning
confidence: 81%